FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK - Ahmad Sahri Romadon Sahri (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to empirically examine the effect of tax sanctions, service quality and tax socialization on taxpayer compliance in paying motor vehicle taxes in the city of Semarang. The population of this study is all motor vehicle tax payers in the city of Semarang. The sample used in this study were 96 respondents.In this study using a purposive sampling. Then the data collection method is through questionnaires and data analysis using SPSS 21. The results of this study indicate that all independent variables, namely tax sanctions, service quality and tax socialization have a positive and significant effect on taxpayer compliance (Y) partially or simultaneously (together). Keywords: Tax Sanctions, Service Quality, Tax Socialization and Taxpayer Compliance